Effect of different materials and undercut on the removal force and stress distribution in circumferential clasps during direct retainer action in removable partial dentures - Mendes Tribst, Joao Paulo [UNESP]; Oliveira Dal Piva, Amanda Maria de [UNESP]; Souto Borges, Alexandre Luiz [UNESP]; Araujo, Rodrigo Maximo [UNESP]; Ferraz da Silva, Joao Mauricio [UNESP]; Bottino, Marco Antonio [UNESP]; Kleverlaan, Cornelis Johannes; Jager, Niek de (Elsevier B.V., 2020)
Objectives. This study aimed to evaluate the effect of different materials and undercut on the removal force and stress distribution in the supporting tooth and in the circumferential clasp used in removable partial prosthesis. Methods. Upper molars prepared for Akers circumferential clasp with retention and opposing arm were modeled, scanned, elaborated with CAD software and the geometries imported in FEA and analyzed. Six different materials were selected for the clasp (Polyamide, Poly-oxymethylene, Polyetheretherketone - PEEK, Gold alloy, Titanium and CoCr) and 3 different undercuts (0.25, 0.50 and 0.75 mm), totaling 18 groups. Results. The clasps presented greater stress in their structure and potentially greater damage to the dental enamel when made with rigid materials and with more undercut; however, they presented greater ability to remain in position. Significance. Polyamide with a higher undercut is an esthetic alternative to rigid metallic clasps. It showed promising behavior because it strongly reduces the damage to the enamel, and even with an undercut of 0.75, the retention is lower than for CoCr with a 0.25 undercut, and this retention might still be sufficient. Polyoxymethylene and Polyetheretherketone (PEEK) are not suitable materials for the clasps, because the maximum stress occurring during removal with higher undercuts is higher than the material strength. (C) 2019 The Academy of Dental Materials. Published by Elsevier Inc. All rights reserved.
Keywords: Removable partial denture; Finite element analysis; Prosthetic dentistry; Retentive force; Clasp; Non-Metal clasp; Retention